Comparative larval morphology in three species of Pleurodeles (Urodela: Salamandridae) - Escoriza, Daniel; Hassine, Jihène Ben (Zootaxa, 2017)
The Ribbed newts (genus Pleurodeles) are endemic to the Iberian Peninsula and northwest Africa (Raffaëlli 2013), and comprise three species: Pleurodeles nebulosus (Guichenot 1850), Pleurodeles poireti (Gervais 1836) and Pleurodeles waltl Michahelles 1830. Pleurodeles nebulosus is found in northern Algeria and Tunisia with an average size of 18 cm, while P. poireti is endemic to the Edough Massif, in northeastern Algeria and is the smallest species, with 12.9 cm in total length (Escoriza et al. 2016; Carranza & Wade 2004). Pleurodeles waltl appears on the Iberian Peninsula and Morocco (García-París et al. 2004). The eastern and western populations of P. waltl although they are not differentiated taxonomically show high levels of genetic divergence (estimated to have occurred 2.0–3.2 Ma; Carranza & Arnold 2003). The individuals of P. waltl attain large sizes (30 cm of total length) and have 8−10 cutaneous glands on both sides (Pasteur 1958), which are absent in other species of the genus.